Ett klick för en bättre värld - Jurjaks,Mathilda; Öhrström,Victoria (2014)
A click for a better world The media landscape has changed along with developments in society. This has resulted in new forms of engagement which has created new opportunities for individuals to express their civic engagement. However, these opportunities are now starting to be questioned. The last years research in social media engagement show an inconsistent picture of the engagement with competing opinions. The aim of this study is to contribute to the research by developing a deeper understanding of civic engagement on Facebook. By exploring the underlying motives to why people engage in activities for social causes on Facebook, the study discusses the significance of civic engagement for the individual as well as for society. Empirical data is collected from three focus group interviews, each with 6 participants. The study has identified two key motives for civic engagement on Facebook; the desire to present oneself in a favorable way and the willingness to make a difference. Moreover, the study reached several conclusions regarding the significance of Facebook engagement. Firstly, engagement enables people to find their identities as individuals as well as citizens. Facebook engagement can also be understood as a new way to participate in society; thus it enables people to express them-selves as citizens. Moreover, civic engagement helps to spread information, raise awareness of social issues, function as an efficient tool to mobilise people and facilitate fast action during crises. Potentially negative implications of the engagement were also identified in the study: individuals find the engagement on Face-book high risk since it take place public, which can result in a non engagement. Furthermore, the fragmentation and information stress caused by Facebook engagement could result in information being filtered out and in misunderstandings of the purpose behind the engagement and the social issues it relates to.
Keywords: sociala medier; Facebook; engagemang; samhällsengagemang; motiv; social media; engagement; civic engagement; motives